Problems in Islamic Religius Education Based on Carol A. Tomlinson’s Differentiation Theory at Elementary School - Miftakhul Himawan; Zahrotul Inayah; Dian Rusydianti; Muhammad Miftah; Moh Sholihuddin (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2026)
Islamic Religious Education (IRE) instruction in elementary schools still faces various challenges that affect the effectiveness of the learning process. This study aims to analyze the problems of IRE learning at Sasmita Edukasi Blora Elementary School based on the perspective of Carol A. Tomlinson’s differentiated instruction theory, which encompasses differentiation of content, process, products, and the learning environment. This study employs a descriptive qualitative approach using field research and a case study design. The results of the study indicate that the challenges in IRE learning are divided into four elements of differentiation. In content differentiation, there is a mismatch between the taught material and students’ readiness, as well as a lack of tiered instructional materials. In process differentiation, there is a dominance of the lecture method, difficulties in managing learning outside the classroom, low student motivation, and the absence of planned differentiated treatment between students with varying learning abilities. In product differentiation, there was a limited selection of tasks given to students, which failed to accommodate their diverse interests and abilities. Meanwhile, in environmental differentiation, there were limitations in classroom space, difficulties in managing nature-based learning, and a lack of learning support facilities such as projectors. This study concludes that the challenges in Islamic Education (IRE) learning at Sasmita Edukasi Elementary School in Blora are not only related to teaching methods but also involve student readiness, learning product variety, and the learning environment. Therefore, the comprehensive implementation of differentiated instruction is a critical need to achieve more inclusive, adaptive, and effective IRE learning.